Using XFEM Techniques to Predict the Damage of aluminum 2024T3 notched under tensile load (Fracture and Structural Integrity, 2019)
The objective of this work is to analyze some geometrical effect to predict the damage of aluminum 2024T3 structure after validate numerical model by experimental test. The mechanical of damage behaviour under tensile tests of several plates with notches of various forms are investigated using an XFEM technique. The finite element analysis is performed to determine the failure load of these plates. Four different form of notched plates in another part of this work are reinforced by a thickness augmentation with different shapes around the notch. The results of the tensile analysis show that the reinforcements gives the best increase in failure load of each plates.
Keywords: Failure load; Damage; Notch; XFEM